2006
DOI: 10.1242/jcs.02890
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of CTCF to the nucleolus inhibits nucleolar transcription through a poly(ADP-ribosyl)ation-dependent mechanism

Abstract: Multiple functions have been reported for the transcription factor and candidate tumour suppressor, CTCF. Among others, they include regulation of cell growth, differentiation and apoptosis, enhancer-blocking activity and control of imprinted genes. CTCF is usually localized in the nucleus and its subcellular distribution during the cell cycle is dynamic; CTCF was found associated with mitotic chromosomes and the midbody, suggesting different roles for CTCF at different stages of the cell cycle. Here we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
85
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(96 citation statements)
references
References 64 publications
10
85
1
Order By: Relevance
“…CTCF has been shown to localize to the nucleolus and repress nucleolar transcription in UR61 cells (33). However, in this study, we found that CTCF positively regulates rRNA gene transcription in HeLa-S3 cells.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…CTCF has been shown to localize to the nucleolus and repress nucleolar transcription in UR61 cells (33). However, in this study, we found that CTCF positively regulates rRNA gene transcription in HeLa-S3 cells.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been reported that translocation of CTCF from nucleoplasm to the nucleolus was observed after differentiation of K562 myeloid cells or induction of apoptosis in MCF7 breast cancer cells (33). Nucleolar protein nucleophosmin/B23 has been shown to interact with CTCF and is present in vivo at insulator sites in the chicken ␤-globin locus (31).…”
Section: Discussionmentioning
confidence: 99%
“…In lymphocyte B cells, increased expression of CTCF is associated with downregulation of c-Myc, resulting in cell growth arrest and cell death [15]. Accumulation of CTCF in the nucleoli is related to growth arrest and apoptosis during differentiation in human K562 myeloid cells and in human breast carcinoma cells, respectively [16,17]. These results suggest that CTCF may be a determinant factor to death signaling pathways in these cells.…”
Section: Introductionmentioning
confidence: 97%
“…Thus, specific phosphorylation of CTCF by the protein kinase CK2 (former casein kinase II) affects CTCF function in transcriptional regulation (15,29). Poly(ADP-ribosyl)ation is another recently discovered modification of CTCF that is important for insulator function (27,67) and nucleolar transcription (60). Posttranslational modifications of CTCF have also been implicated in human myeloid cell differentiation (14).…”
mentioning
confidence: 99%